ANALISIS HUBUNGAN RASIO KONSENTRASI , INTENSITAS IKLAN, DAN PROFITABILITAS INDUSTRI KOSMETIK DI INDONESIA - YULIA SAFTIANA (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
In this paper, we are going to analysis the stucture, conduct and performance of Indonesian cosmetics corporation registered in Bursa Efek Indonesia (BEI).    Industrial Structure is measured by Concentration Ratio (CR).Industrial conduct is measured by advertising intensity.  The performance of industry is measured by using the average of Return on Sales (ROS) for industry. The influence of consentration ratio (CR) to advertising intensity and to the profitability industry, and The influence of advertising intensity and to the profitabiliy industry were analyzed using descriptive analysis.  The result of this study showed the influence of the concentration ratio to advertising intensity and to the profitability industry, and The influence of advertising intensity and to the profitabiliy on cosmetics industry registered  in Bursa Efek Indonesia (BEI)is not signifikan.